1985
DOI: 10.2307/2000177
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Semisimple Algebraic Monoids

Abstract: Abstract.Let A' be a semisimple algebraic monoid with unit group G. Associated with E is its polyhedral root system (X, 0, C), where X = X(T) is the character group of the maximal torus T c G, $ c X(T) is the set of roots, and C = X(T) is the character monoid of T c E (Zariski closure).The correspondence £-»(A\ O, C) is a complete and discriminating invariant of the semisimple monoid £, extending the well-known classification of semisimple groups. In establishing this result, monoids with preassigned root data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…It is easily showed that every complete symmetric variety is covered by simple open symmetric G-subvarieties whose closed orbits are complete. We generalize the results of Timashev (see [16]) and Renner (see [12]) on the equivariant embeddings of reductive groups. The idea of the proof is the following one.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…It is easily showed that every complete symmetric variety is covered by simple open symmetric G-subvarieties whose closed orbits are complete. We generalize the results of Timashev (see [16]) and Renner (see [12]) on the equivariant embeddings of reductive groups. The idea of the proof is the following one.…”
supporting
confidence: 61%
“…Observe that G acts on End C (V (µ i )) ⊂ End C (V ) and the action coincides with the one over V ⊗ V * through the canonical isomorphism End C (V ) ∼ = V ⊗ V * . Also Renner (see [12]) considers the case where G/H is isomorphic to a reductive groupĠ, but he studies the affine (normal) equivariant embeddings ofĠ with a G-fixed point. He classifies the smooth ones in the case where the center ofĠ has dimension 1 and the derived group ofĠ is simple.…”
Section: Theorem 21 Let X Be a Simple Smooth Symmetric Variety Withmentioning
confidence: 99%
“…We will further asssume that the group of units G of M is reductive. Then by [6,10], M is unit regular, i.e. M = E(M)G. Here E(M) is the idempotent set of M. We fix a maximal torus T of G. If Y Ç E(T), then we let CrG(Y) = {aE G\ae = eae for all e E Y}, ClG(Y) = {a E G\ea = eae for all e € T}.…”
Section: Preliminariesmentioning
confidence: 99%
“…This means [1,3] that the unipotent radical of G is trivial. Then by [6,10], M is unit regular, i.e. M = E(M)G where E -E(M) = {e E M\e2 = e}.…”
mentioning
confidence: 99%
“…Thus it seems reasonable in trying to extend representation theory from reductive groups to reductive monoids to look first at the case when M is normal. Second, L. Renner [14] has obtained a classification theorem for such monoids under the additional assumptions that the center Z(M ) is 1-dimensional and that M has a zero element. Renner calls such algebraic monoids semisimple and proves that they are classified by data of the form (X(T ), Φ, X(T )), where (X(T ), Φ) is the usual root data which classifies the reductive group G and X(T ) is the character group of the closure (in M ) of the maximal torus T .…”
Section: Introductionmentioning
confidence: 99%